KAJIAN PERHITUNGAN GLOBAL GROSS TRAVEL PROPENSITY (GTP) DAN COUNTRY POTENTIAL GENERATION INDEX (CPGI) 2016 - Addin Maulana (Jurnal Pariwisata Pesona, 2019)
This study is intended to provide an overview of the position of countries in the world based on Gross Travel Propensity (GTP) and the Country Generation Potential Index (CPGI), which are expected to become one of the considerations in determining the potential market for tourism development. This study uses a formula developed by Hurdman. Using this formula, the results as follows: 58 from 89 countries with CPGI of more than 1.0 were obtained, indicating that this country produced more international tourists than expected from their population; Of these 58 countries, 23 countries have higher GTP than their country's population, meaning that these countries have a population with a tendency to travel abroad high, so that it will be very potential to put them as the main market; A total of 17 countries have more than half the GTP population, allowing these countries to be considered as secondary markets; While 18 other countries have GTP less than ½ of the population, so it has a low potential to be considered as a market. This study provides recommendations to the government in determining the country to be a target market for international tourists, from the perspectives aspect of the population and the number of tourist trips abroad produced in the country.